2010
DOI: 10.1007/s10597-009-9283-7
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Outcomes Among Homeless Clients with Serious Mental Illness: Comparing Housing First with Treatment First Programs

Abstract: The Housing First (HF) approach for homeless adults with serious mental illness has gained support as an alternative to the mainstream "Treatment First" (TF) approach. In this study, group differences were assessed using qualitative data from 27 HF and 48 TF clients. Dichotomous variables for substance use and substance abuse treatment utilization were created and examined using bivariate and logistic regression analyses. The HF group had significantly lower rates of substance use and substance abuse treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
157
0
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(176 citation statements)
references
References 18 publications
5
157
0
14
Order By: Relevance
“…When comparing Housing First to other permanent supportive housing programs, data have shown that persons in Housing First programs are less likely to use substances over time, have greater residential stability, and have lower associated costs. 8,9 Housing status also appears to have a positive impact on decreasing medical service usage in both inpatient and outpatient settings. While the results of this study did not yield statistically significant differences in this area, the financial implications of our findings are important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing Housing First to other permanent supportive housing programs, data have shown that persons in Housing First programs are less likely to use substances over time, have greater residential stability, and have lower associated costs. 8,9 Housing status also appears to have a positive impact on decreasing medical service usage in both inpatient and outpatient settings. While the results of this study did not yield statistically significant differences in this area, the financial implications of our findings are important.…”
Section: Discussionmentioning
confidence: 99%
“…Through housing stabilization and the availability of services, many clients of Housing First programs are more successful when measured on outcomes of physical and mental health, substance abuse, health care utilization, and access to mainstream services including social security benefits and Medicare/Medicaid enrollment. 8 When assessed on its overall impact, Housing First has the potential to be one of the most effective programs to address chronic homelessness by reducing overall cost to the community; successfully transitioning homelessness into stable housing; improving health outcomes; and increasing acceptance of medical care as well as mental health and substance abuse treatment services.…”
mentioning
confidence: 99%
“…Most studies also focus on the effectiveness of specific housing models in helping homeless persons to remain housed, often in the context of those with serious mental illness and addictions (Bebout et al, 1997;Kyle and Dunn, 2008). Much less attention has been given to the effect of homelessness on health and wellbeing several years later, or in older age (Padgett et al, 2011;Shibusawa and Padgett, 2009). A longitudinal study would ideally provide the best insight into the long-term health outcomes of homelessness, but there are methodological limitations that stand in the way.…”
Section: Introductionmentioning
confidence: 99%
“…So important is this issue, it was identified in the initial 1992 Australian National Mental Health Strategy (NMHS). It has since been repeatedly acknowledged that the provision of appropriate housing enhances the effectiveness of treatment and rehabilitation services and is necessary if treatment gains are to be maintained (Padget, Stanhope, Henwood, & Stefancic, 2010).Without strenuous attention to appropriate housing, the morbidity and mortality arising from mental illness in the community will continue to be compounded. The purpose of this research was to achieve a deeper understanding of the housing environments inhabited by people with mental illness in the community following a period of institutionalization.…”
Section: Introductionmentioning
confidence: 99%